Blood sampling in adult critical care: a mixed methods study. (May 2022) - Lennox, Sarah; Bench, Suzanne
Abstract: There are few studies exploring blood sampling practice in critical care. In particular, the views of nursing staff are missing from the literature. The aim of this mixed methods study was to understand blood sampling practice at a single centre National Specialist Orthopaedic NHS trust in London, England. Following an audit of sampling practice over a four-week period, two focus group discussions explored nurses' views and experiences. Daily blood samples were in keeping with volumes reported in other studies of a similar size and nature, with routine sampling practice common. Although we did not seek associations between data sets, the daily reported losses from blood sampling may be a contributory factor in patients' overall post-operative haemoglobin fall resulting in blood transfusion. Four key themes emerged from the qualitative focus groups: training and responsibility, influences and impacts, nursing time and errors. The routine nature of blood sampling practice may be specific to the elective setting, but raises questions around the need for a more patient centred, needs based approach. In addition to reducing the number of potentially unnecessary tests, small-volume phlebotomy tube (SVPT), closed sampling systems and increased use of Point of Care Testing (POCT) should be considered. Education and development of clear localised protocols could also help reduce the amount of unnecessary blood taken from patients in elective adult critical care settings.